Multimodal drone swarm for search and rescue mission - Kopyt, Antoni; Czaplińska, Anna (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
A drone swarm is a large group of cooperating unmanned aerial vehicles that exhibit some form of autonomy. This structure allows for an increase in the complexity of performed tasks while limiting the mental load put on the operator. One field where drone swarms can prove especially useful is search and rescue – they can reduce the mission time and improve personnel safety. This paper presents an offline mission planning module composed of a set of mission scenarios designed to aid rescuers in a disaster area: internet provision, area search, and patrol. The internet connection is provided by a hexagonal mesh of drones spanning the area. A method for continuous drone replacement and charging is presented. The area search scenarios are based on a cooperative subarea search by groups of drones using a lawnmower pattern. The patrol scenarios feature continuous area patrol by an unstructured flock of drones and formation boundary patrol (circle formation and V-shape). The developed solutions are an easy-to-implement base for multipurpose search and rescue drone swarm solutions. Their functionality can be expanded by the ground control station as desired.